Cadm1 is a metastasis susceptibility gene that suppresses metastasis by modifying tumor interaction with the cell-mediated immunity. - Farhoud Faraji; Yanli Pang; Renard C Walker; Rosan Nieves Borges; Li Yang; Kent W Hunter (PLoS Genetics)
Metastasis is a complex process utilizing both tumor-cell-autonomous properties and host-derived factors, including cellular immunity. We have previously shown that germline polymorphisms can modify tumor cell metastatic capabilities through cell-autonomous mechanisms. However, how metastasis susceptibility genes interact with the tumor stroma is incompletely understood. Here, we employ a complex genetic screen to identify Cadm1 as a novel modifier of metastasis. We demonstrate that Cadm1 can specifically suppress metastasis without affecting primary tumor growth. Unexpectedly, Cadm1 did not alter tumor-cell-autonomous properties such as proliferation or invasion, but required the host's adaptive immune system to affect metastasis. The metastasis-suppressing effect of Cadm1 was lost in mice lacking T cell-mediated immunity, which was partially phenocopied by depleting CD8(+) T cells in immune-competent mice. Our data show a novel function for Cadm1 in suppressing metastasis by sensitizing tumor cells to immune surveillance mechanisms, and this is the first report of a heritable metastasis susceptibility gene engaging tumor non-autonomous factors.